If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -23 + -37Y = 3 Reorder the terms: -23 + Y + -37Y = 3 Combine like terms: Y + -37Y = -36Y -23 + -36Y = 3 Solving -23 + -36Y = 3 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -36Y = 3 + 23 Combine like terms: -23 + 23 = 0 0 + -36Y = 3 + 23 -36Y = 3 + 23 Combine like terms: 3 + 23 = 26 -36Y = 26 Divide each side by '-36'. Y = -0.7222222222 Simplifying Y = -0.7222222222
| p-18=18(h-6) | | 5x-14=16x | | p-18=23/3(h-6) | | 1x+34=26 | | 2x^2-12x+68=100 | | p=23/6h+18 | | 0=-4/5x-4 | | 7x+10=3x+78 | | -5t^2+40t+1.2=60 | | 5x+26=125-5x | | 24/34=4y+12/85 | | 45X^2+15X+5=0 | | 7/9=x/108 | | x^7z^5/x^4z | | 1/5u-5/2=-7/3 | | 18(t+4)=9t/9 | | y=-7/8(-7)+7 | | 50=3(5+16)-2(s-2) | | C^2+4b= | | -31*-18+3x=38 | | (7/y+6)=6 | | -7/8w=35 | | -4/3*u=12 | | 5(y-1)=2y+1 | | -3/4*u=12 | | Z-10=-18 | | 12-2x6+2/2=X | | 2+5-3*4/2 | | 2k+3=-17 | | p-25=15/4(h-18) | | -2(w-5)=-4w+26 | | 4y-3+y+20=6y+20-4y |